2015
DOI: 10.1371/journal.pone.0132966
|View full text |Cite
|
Sign up to set email alerts
|

Cryptochromes and Hormone Signal Transduction under Near-Zero Magnetic Fields: New Clues to Magnetic Field Effects in a Rice Planthopper

Abstract: Although there are considerable reports of magnetic field effects (MFE) on organisms, very little is known so far about the MFE-related signal transduction pathways. Here we establish a manipulative near-zero magnetic field (NZMF) to investigate the potential signal transduction pathways involved in MFE. We show that exposure of migratory white-backed planthopper, Sogatella furcifera, to the NZMF results in delayed egg and nymphal development, increased frequency of brachypterous females, and reduced longevity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 58 publications
(89 reference statements)
0
31
0
Order By: Relevance
“…Following the previously used workflow and standards for one generation of exposure of rice planthoppers (Wan et al, 2015b). We exposed N. lugens individuals to NZMF vs. GMF conditions for either one generation (from mated F0 females to newly emerged F1 adults) or less than one generation (from mated F0 females to older nymphs) because their long-distance migration is usually initiated after adults emerge following at least one generation of local reproduction (Cheng et al, 2003).…”
Section: Magnetic Field Setups and Insect Exposuresmentioning
confidence: 99%
See 3 more Smart Citations
“…Following the previously used workflow and standards for one generation of exposure of rice planthoppers (Wan et al, 2015b). We exposed N. lugens individuals to NZMF vs. GMF conditions for either one generation (from mated F0 females to newly emerged F1 adults) or less than one generation (from mated F0 females to older nymphs) because their long-distance migration is usually initiated after adults emerge following at least one generation of local reproduction (Cheng et al, 2003).…”
Section: Magnetic Field Setups and Insect Exposuresmentioning
confidence: 99%
“…Instar durations to the adult stage (instars 1-5) were measured in days as previously described for the white-backed planthopper, Sogatella furcifera (Wan et al, 2015b). Differentiating between the sexes of juveniles is very difficult and was not attempted for the molecular, behavioral, and biochemical assays of nymphs described below.…”
Section: Developmental Periods Of Nymphs and Body Weight Of Newly Emementioning
confidence: 99%
See 2 more Smart Citations
“…Our work with migratory white-backed planthopper, Sogatella furcifera , showed that the absence of GMF can affect the expression of important migration-related behaviours, potentially through Cry-mediated hormone signaling. This includes changes in positive phototaxis which is critical for the ascent process, and flight capacity which is energetically-intensive and one of the main parameters used to assess migration ability [9, 18]. Additionally, previous work in migratory birds showed that changes in GMF information (both intensity and direction) over the migration route can affect their fuelling decisions and migratory restlessness [19-22].…”
Section: Introductionmentioning
confidence: 99%